2009
DOI: 10.1021/ma900205s
|View full text |Cite
|
Sign up to set email alerts
|

Determination of theFdddPhase Boundary in Polystyrene-block-polyisoprene Diblock Copolymer Melts

Abstract: We determined the phase boundary of the Fddd phase in the phase diagram of polystyreneblock-polyisoprene (SI) diblock copolymer by using small-angle X-ray scattering (SAXS) and transmission electron microscopy (TEM). We prepared eight SI diblock copolymers having different volume fractions of polyisoprene, f PI , in the range of 0.627 e f PI e 0.653 by living anionic polymerization. At the lowest f PI , 0.627, SI diblock copolymer showed only the disorder-lamellar (L) transition without any order-order transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 19 publications
3
43
0
Order By: Relevance
“…Kim et al recently reported on order-order transitions from or to the Fddd phase in the polystyrene-block-polyisoprene (PS-b-PI) bulk system. 12,13 In the diblock copolymer, the morphology was observed in a very narrow region between the In the tripod elementary unit in the Fddd phase, three tripods are on the same plane (a-plane, dashed line rectangle), and the 4 th one is twisted (bplane, dotted line rectangle) by an angle, q. The segments on the a-plane, on the b-plane and parallel to the c axis are color-coded as black, dark gray and gray, respectively.…”
Section: 8mentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al recently reported on order-order transitions from or to the Fddd phase in the polystyrene-block-polyisoprene (PS-b-PI) bulk system. 12,13 In the diblock copolymer, the morphology was observed in a very narrow region between the In the tripod elementary unit in the Fddd phase, three tripods are on the same plane (a-plane, dashed line rectangle), and the 4 th one is twisted (bplane, dotted line rectangle) by an angle, q. The segments on the a-plane, on the b-plane and parallel to the c axis are color-coded as black, dark gray and gray, respectively.…”
Section: 8mentioning
confidence: 99%
“…Samples were prepared at every 10 C up to 150 C. C. It shows a wellaligned structure which is analogous to one of the cross-sectional views of the Fddd phase reported earlier. 13,46 In addition, the layer-like structure developed adjacent to the free surface is also of interest. The TEM image shows a well-developed regular pattern, but it is not sufficient to elucidate the detailed structure from such a projected image.…”
mentioning
confidence: 99%
“…Recent SCFT calculations have resolved another fifth stable phase 6 of cocontinuous morphology, which has subsequently been observed in experiments. 7 The incorporation of an additional species to a DBC melt adds more dimensions to the phase diagram, although it also opens up the possibility of macrophase separation. Nevertheless, the new dimensions potentially allow a larger window of stability of the desired phases and perhaps conditions more accessible via experiments.…”
Section: Introductionmentioning
confidence: 99%
“…3b) [18][19][20] is another equilibrium morphology discovered recently in SI diblock copolymers with the polyisoprene-rich composition around f PI ¼ 0.65, where f PI is the volume fraction of polyisoprene component. Fddd phase was found in the weak segregation region in the f PI range between LAM and Ia3d.…”
Section: Phase Behavior Of Diblock Copolymersmentioning
confidence: 83%
“…The advantage of SAXS study is that one can use melt or solution samples if an appropriate sample holder is used. Therefore, Ia3d and Fddd in the weak segregation regime as well as the OOT between them can be studied [18][19][20]. Here, it should be noted that SAXS observes the structures averaged in space and time, although the microdomain structures in the weak segregation regime are dynamic.…”
Section: Analysis Of Microdomain Structuresmentioning
confidence: 98%